Changes in Sexual Behavior, PrEP Adherence, and Access to Sexual Health Services Because of the COVID-19 Pandemic Among a Cohort of PrEP-Using MSM in the South. (1st May 2021) - Pampati, Sanjana; Emrick, Kayla; Siegler, Aaron J.; Jones, Jeb
Abstract : Background: The coronavirus disease 2019 (COVID-19) pandemic has had unforeseen consequences on the delivery of HIV and sexually transmitted disease (STD) prevention services. However, little is known about how the pandemic has impacted pre-exposure prophylaxis (PrEP)-using men who have sex with men (MSM). Methods: Data come from an online cohort of PrEP-using MSM in the Southern United States from October 2019 to July 2020. Participants were administered 10 surveys in total, including 1 ad hoc survey specifically on COVID-19. We conducted a cross-sectional analysis of this ad hoc survey (n = 56) and present changes in sexual behaviors and utilization of and access to sexual health services. Using linear mixed-effect regression models, we also analyzed data from the larger cohort and document how sexual behaviors and PrEP use varied longitudinally across several months. Results: A fifth of participants discontinued or changed how often they take PrEP because of COVID-19. A quarter of the cohort documented challenges when attempting to access PrEP, HIV testing, or STD testing. For all sexual behaviors examined longitudinally—number of male sexual partners, anal sex acts, condomless anal sex, and oral sex (all measured in the past 2 weeks)—there was a decrease from February to April followed by an increase from April to June. Discussion: Our findings suggest reduced access to and utilization of STD and HIV services coupled with a continuation of behaviors which confer STD/HIV risk. Ensuring appropriate delivery of STD/HIV prevention services during this pandemic is imperative.